Input for a rapid risk assessment methodology for flood-based for existing flood-prone bridges - Sháněl, Zdeněk; Yurdakul, Özgür; Řoutil, Ladislav; Pregnolato, Maria (Fédération Internationale du Béton (fib) - International Federation for Structural Concrete, 2024)
A large portfolio of bridges is managed by transport infrastructure managers, often with limited resources. Most bridges in the Czech Republic are already in the latter half of their service life. Simultaneously, extreme weather conditions pose a threat to their structural integrity and the safety of road traffic. Identifying flood risk is essential to prioritizing intervention strategies. However, a quick guideline for rapid flood risk-based assessment of bridges in the Czech Republic is not available for infrastructure managers. Therefore, this paper proposes a methodology for assessing the risk of existing bridges under flood hazard, combining factors such as flood hazard, bridge vulnerability, and potential consequences. First, bridges from four regions of the Czech Republic were selected, and a comprehensive dataset was created. The vulnerability assessment relies on the available dataset, incorporating fundamental details such as bridge geometry, location, and construction type. The flood hazard was then evaluated by considering topographical, geological, and hydrological inputs. All data used for the flood risk-based assessment are available online, which is summarized in this paper. The accessibility of the data is of great benefit to managers who will implement the guidance produced by the flood risk-based assessment.
Keywords: Risk assessment; Flood; Management; Bridge; Hazard